Respuesta :
The completing the square method is important when transforming a quadratic equation to [tex](x - a)^2 =b[/tex] form. The values of a and b are 4 and 3
Given:
[tex]x^2 - 8x + 13 = 0[/tex]
Subtract 13 from both sides
[tex]x^2 - 8x + 13 -13= 0-13[/tex]
[tex]x^2 - 8x= -13[/tex]
-------------------------------------------------------------
Next, we perform the following operations
Take the coefficient (k) of x
[tex]k = -8[/tex]
Divide k by 2
[tex]k/2 = -8/2[/tex]
[tex]k/2 = -4[/tex]
Square both sides
[tex](k/2)^2 = (-4)^2[/tex]
[tex](k/2)^2 = 16[/tex]
Back to the equation, we add 16 to both sides
-------------------------------------------------------------
[tex]x^2 - 8x= -13[/tex]
[tex]x^2 - 8x + 16 = -13 +16[/tex]
[tex]x^2 - 8x + 16 =3[/tex]
Expand the left-hand side
[tex]x^2 - 4x -4x+ 16 =3[/tex]
Factorize
[tex]x(x - 4) -4(x- 4) =3[/tex]
Factor out x -4
[tex](x - 4) (x- 4) =3[/tex]
Express as squares
[tex](x - 4)^2 =3[/tex]
Given that:
[tex](x - a)^2 =b[/tex]
By comparison:
[tex]a =4;\ b =3[/tex]
The values of a and b are 4 and 3, respectively.
Read more at:
https://brainly.com/question/9339531